2000
DOI: 10.2134/agronj2000.922329x
|View full text |Cite
|
Sign up to set email alerts
|

Row Spacing, Plant Population, and Cultivar Effects on Grain Amaranth in the Northern Great Plains

Abstract: An understanding of plant response to row spacing and plant density is important in developing effective production systems for new crops. Optimum row spacing and plant population for grain amaranth (Amaranthus spp.) production in the northern Great Plains was evaluated at Prosper and Williston, ND, over 6 station‐years. Amaranth cultivars K283, K343, K432, and MT‐3 were established at populations of 74 000, 173 000, and 272 000 plants ha−1 in 30‐ and 76‐cm row spacings. Grain and biomass yield, plant height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
40
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 5 publications
13
40
2
7
Order By: Relevance
“…However, no significant impacts on evaluated yield and quality traits could be noted. Similar grain yields of the tested density range correspond to the findings of other authors (Myers 1996, Henderson et al 2000. In contrast to other findings (Andrade andFerreiro 1996, Glowienke andKuhn 1998), the proximate analysis of tested grain did not reveal any plant density effects.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, no significant impacts on evaluated yield and quality traits could be noted. Similar grain yields of the tested density range correspond to the findings of other authors (Myers 1996, Henderson et al 2000. In contrast to other findings (Andrade andFerreiro 1996, Glowienke andKuhn 1998), the proximate analysis of tested grain did not reveal any plant density effects.…”
Section: Resultssupporting
confidence: 89%
“…Guillen-Portal et al (1999) established grain amaranth in the wide range of 4-200 plants/m 2 on dry lands of Nebraska and achieved maximum yield at 47 plants/m 2 . Henderson et al (2000) found no yield response to populations between 7 and 27 plants/m 2 in Dakota. Neither did Myers (1996) with seeding rates from 0.28 to 4.40 kg/ha in Columbia.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Greenhouse experimental data in quinoa showed that optimal plant populations varies from 30 plants m -2 [58] to an optimal plant population of 140 plants m . From variable data we can stress that in A. cruentus cultivars would be recommended above 30-cm row spacing and populations of 74000 and 272000 plants ha -1 [40].…”
Section: Sowingmentioning
confidence: 97%
“…Amaranth is used as an ornamental plant, as forage, and has potential use in the cosmetic industry (O'Brien and Price, 1983). Its cultivation is gaining importance in the USA (Henderson et al, 2000), and Canada (Gélinas and Seguin, 2008). In Mexico, amaranth crop is becoming important again, thanks to the preservation of its cultivation on a small scale by farmers, but its production has potential growth (Becerra, 2000) with a present area of 3,022 ha.…”
Section: Introductionmentioning
confidence: 99%